The Distribution Pattern of Traditional Chinese Medicine Syndromes in 549 Patients with Type 2 Diabetes - Zhang GD (Dove Medical Press, 2021)
Ge-Di Zhang,1,* Xi-Xi Liu,2,* Jia-Lang Liang,3 Qi-Ming Hu4 1Department of Endocrinology, Yuncheng Hospital of Traditional Chinese Medicine, Yuncheng, 274700, People’s Republic of China; 2Department of Endocrinology, Yichun Hospital of Traditional Chinese Medicine, Yichun, 336000, People’s Republic of China; 3Department of Endocrinology, Guangdong Integrated Traditional Chinese and Western Medicine Hospital, Foshan, 528000, People’s Republic of China; 4Department of Endocrinology, Affiliated Hospital of Jiangxi University of Traditional Chinese Medicine, Nanchang, 330000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qi-Ming HuDepartment of Endocrinology, Affiliated Hospital of Jiangxi University of Traditional Chinese Medicine, No. 445 of Bayidadao Street, Donghu District, Nanchang, 330000, People’s Republic of ChinaTel +86 79107702803Email huqimingqw_as@163.comObjective: This study aimed to summarize the distribution pattern of traditional Chinese medicine (TCM) syndromes in patients with type 2 diabetes mellitus (T2DM).Methods: The frequency, characteristics and distribution of all TCM syndromes of 549 patients with T2DM were analyzed.Results: The average age of T2DM onset was higher in women than in men (ie, men experienced earlier onset). The distribution of TCM syndromes, in order of frequency, was as follows: damp-heat trapping spleen (including spleen deficiency and dampness, damp heat due to spleen deficiency, and qi weakness due to spleen deficiency) (58.29%), qi-yin deficiency (16.03%), deficiency of yin and excessive heat (12.93%), blood stasis in collaterals (9.41%), and yin-yang deficiency (3.21%). The physical intensity of patients’ occupational activity was mainly light (49.6%), followed by heavy (31.4%) and moderate (19.0%).Conclusion: Damp-heat trapping spleen is the most common TCM syndrome in patients with T2DM, with damp heat due to spleen deficiency the most significant subtype. This syndrome tends to occur in people over the age of 60 and those undertaking too much or too little physical activity in their occupational activities. The traditional “three more and one less” symptoms do not adequately describe the clinical symptoms of T2DM.Keywords: type 2 diabetes, TCM syndrome differentiation, damp heat due to spleen deficiency, epidemiology, clinical symptoms